Pengajaran Kitab Matan Abu Syuja’ untuk Meningkatkan Maharah Qiro’ah Siswa Kelas XI Madrasah Aliyah Islam Ngruki Tahun Ajaran 2024/2025 - Hasib Adam Zulva (Sekolah Tinggi Islam Al-Mukmin (STIM) Surakarta, 2024)
This study discusses the teaching of the Kitab Matan Abu Syuja' to improve the maharah qiro'ah (reading skills) of class XI D students at MA Islam Al-Mukmin Ngruki, who face difficulties in reading unvowelled Arabic texts and understanding sentence structure. A qualitative descriptive research method was used with data collection techniques including observation, interviews, and documentation. The results show an improvement in reading skills, with an average score of 81.94, the highest score of 95.1, and the lowest score of 70. The conclusion emphasizes that the use of the Kitab Matan Abu Syuja' is effective in enhancing the ability to read classical Arabic texts, and it contributes to the development of Arabic language teaching methods at madrasahs, especially in using classical texts to improve maharah qiro'ah